Oxidation of Nitrate Ions at a Platinum Anode - RK, Bayramov (Journal of Engineering and Applied Sciences Technology, 2025)
The analysis of available works in the literature, including our own, was carried out, on the basis of which this review article was prepared. The interest shown in the processes of oxidative synthesis at high anodic potentials is associated with the production of various types of organic and inorganic, including mixtures of organo-inorganic compounds. The problem of electrochemical introduction of the NO3 group into the molecules of organic and inorganic compounds, which are valuable products used in various fields of technology, is relevant. The electrochemical route to the synthesis of such compounds is complicated by the fact that, unlike perchloric and sulfuric acids, the anodic behavior of NO3 - has not been sufficiently studied. One of the reasons for this is the impossibility of obtaining reliable experimental data when using electrochemical cells in which the interelectrode spaces are separated by a glass porous diaphragm. The products of cathodic reduction, penetrating through the diaphragm into the anolyte, are oxidized by oxygen formed at the anode and significantly affect the reliability of the data obtained, in particular, the current yield (CO) of oxygen. Electrochemical cells in which the interelectrode spaces are separated by cation-exchange membranes have been developed and manufactured for the first time. In this case, the possibility of reduction products getting into the anolyte is excluded, which leads to reliable results. Only electrochemical cells of a new design, allowing reliable data to be obtained, were used in the studies. The direct (radiochemical) method proved the participation of nitrate ions in the anodic process - the oxygen evolution reaction (OER). It is shown that NO3 ions participate in the OER in two ways. The analysis of the complex of the obtained data made it possible to propose a mechanism for the oxidation of nitrate ions.